Growth mechanism and electrochemical properties of hierarchical hollow SnO2 microspheres with a "chestnut" morphology. Issue 43 (23rd October 2017) - Hu, Huating; Wu, Liming; Gebhardt, Paul; Zhang, Xiaofei; Cherevan, Alexey; Gerke, Birgit; Pöttgen, Rainer; Balducci, Andrea; Passerini, Stefano; Eder, Dominik
Abstract : This work provides an in-depth study on the growth, crystallization and performance of hollow SnO2 spheres for Li-ion/Na-ion batteries. Abstract : Hierarchical hollow microspheres (HHMSs) constitute a very popular class of materials for use as drug-delivery carriers, photocatalysts and electrode materials in batteries, owing to their large, porous surface area and mechanical integrity during intercalation reactions. Here, we used a template- and additive-free hydrothermal route to prepare an unusually shaped SnO2 material that comprises a hollow spherical morphology with uniform diameters and very thin petal-like nano-sheets grown perpendicularly on the sphere's surface, resembling a "chestnut cupule". We thoroughly investigated the formation mechanism by 119 Sn Mössbauer spectroscopy, powder X-ray diffraction and X-ray photoelectron spectroscopy. Key to this process is the ultrasonic pre-treatment of an aqueous SnCl2 solution, followed by Ostwald "inside-out" ripening upon hydrothermal processing. This unique morphology has greatly improved the storage capacity and cycling performance of SnO2 as an anode material for lithium and sodium ion batteries compared with conventional SnO2 materials.